Hybrid Hegemonic Masculinities: Interrogating Men’s Intervention Programming - Chris M. Vidmar (Socius)
Reporting on an ethnography of a profeminist batterer intervention program (BIP), this article details how the theory of hybrid hegemonic masculinities can help understand processes and outcomes in men’s interventions. The BIP exalts a liberal masculinity that explains men’s abuse as caused by patriarchal ideologies. The author refers to this locally dominant masculinity as progressive hybrid masculinity, as it discursively distances men who adopt it from global hegemonic masculinity by subordinating “toxic masculinity,” reframes emotional expressiveness and empathy as masculine through a discourse of power, and covertly shores up men’s structural power through reification of conventional masculine roles and values. Observational data, triangulated with interviews, reveal that men’s engagement with and enacting of this hybrid masculinity moderated program outcomes, resulting in attitudes ranging from egalitarian to oppressive. The author situates progressive hybrid masculinity as a hybrid masculinity functioning as a local hegemonic masculinity, adding to the debate regarding the synthesis of these prominent frameworks.